Simple acyclic molecules containing a single charge-assisted O–H group can recognize anions in acetonitrile : water mixtures. Issue 12 (15th March 2021) - Goodwin, Rosemary J.; Blyth, Mitchell T.; Fung, Alfred K. K.; Smith, Leesa M.; Norcott, Philip L.; Tanovic, Sara; Coote, Michelle L.; White, Nicholas G.
Abstract : Simple cationic compounds containing O–H hydrogen bond donors bind anions very strongly in acetonitrile, and with moderate strength in 9 : 1 acetonitrile : water. Abstract : Hydroxypyridinium and hydroxyquinolinium compounds containing acidic O–H groups attached to a cationic aromatic scaffold were synthesized, i.e. N -methyl-3-hydroxypyridinium (1 + ) and N -methyl-8-hydroxyquinolinium (2 + ). These very simple compounds are capable of binding to chloride very strongly in CD3 CN and with moderate strength in 9 : 1 CD3 CN : D2 O. Comparison with known association constants reveals that 1 + and 2 + bind chloride in CD3 CN or CD3 CN : D2 O with comparable affinities to receptors containing significantly more hydrogen bond donors and/or higher positive charges. Crystal structures of both compounds with coordinating anions were obtained, and feature short O–H⋯anion hydrogen bonds. A receptor containing two hydroxyquinolinium groups was also prepared. While the low solubility of this compound caused difficulties, we were able to demonstrate chloride binding in a competitive 1 : 1 CD3 CN : CD3 OD solvent mixture. Addition of sulfate to this compound results in the formation of a crystallographically-characterised solid state anion coordination polymer.